Sectoral digital intensity and GDP growth after a large employment shock: A simple extrapolation exercise. (5th January 2022) - Gallipoli, Giovanni; Makridis, Christos A.
Abstract: We introduce a state‐dependent algorithm with minimal data requirements for predicting output dynamics as a function of employment across industries and locations. The method generalizes insights of Okun (1963) by leveraging measures of industry heterogeneity. We use the algorithm to examine gross domestic product (GDP) dynamics following the COVID‐19 pandemic of 2020, delivering informative projections of aggregate and sectoral output. Because the pandemic curtailed the ability to perform certain tasks at work, our application examines whether greater reliance on digital technologies can mediate employment and productivity losses. We use industry‐level indices of digital task intensity and ability to work from home, together with publicly available data on employment and GDP for Canada, to document that: (i) employment responses after the shock's onset are milder in digitally intensive sectors and (ii) conditional on the size of employment changes, GDP responses are less extreme in digitally intensive sectors. Our projections indicate a return to pre‐crisis aggregate output within eight quarters of the initial shock with significant heterogeneity in recovery patterns across sectors. Résumé: Intensité numérique sectorielle et croissance du PIB après un important choc sur le plan de l'emploi : un simple exercice d'extrapolation . Nous utilisons un algorithme dépendant de l'état avec des exigences minimales en matière de données pour prédire les dynamiques de production comme fonction de l'emploi dans plusieurs industries et lieux. La méthode généralise les observations de Okun (1963) en mettant à profit les mesures d'hétérogénéité de l'industrie. Nous utilisons l'algorithme pour examiner les dynamiques du produit intérieur brut (PIB) après la pandémie de COVID‐19 de 2020, produisant ainsi des projections informatives sur la production globale et sectorielle. Puisque la pandémie a réduit la capacité d'exécuter certaines tâches au travail, notre application examine si le fait de miser davantage sur les technologies numériques peut atténuer les pertes d'emplois et de productivité. Nous avons recours à des indices à l'échelon de l'industrie sur l'intensité des tâches numériques et la capacité de travailler à la maison, de concert avec les données disponibles au public sur l'emploi et le PIB au Canada, en vue de documenter que : i) les réponses de l'emploi après le début du choc sont plus tempérées dans les secteurs à intensité numérique et ii) de façon conditionnelle à l'ampleur des changements sur l'emploi, les réponses du PIB sont moins extrêmes dans les secteurs à intensité numérique. Nos projections indiquent un retour à la production globale antérieure à la crise dans les huit trimestres suivant le choc initial ainsi qu'une hétérogénéité significative dans les modèles de reprise dans l'ensemble des secteurs.